Unterwegs in eine Welt des Verstehens.Gehörlosenbildung in Hamburg vom 18. Jahrhundert bis in die Gegenwart - Groschek, Iris (Hamburger Historische Forschungen, 2008)
This book presents the history of deaf education in Hamburg for the first time: from Samuel Heinicke's School for the Deaf in phonetic language to the recognition of German Sign Language. The life of deaf people in Hamburg from the 18th century to the present day is vividly depicted.